(Rubba): its rulings and grammatical opinions on it - Mouhamed, Khalf Alah Nady (Journal of Humanities & Social Sciences, 2020)
This research deals with one of the letters of the meanings in which there was a dispute between linguists and grammarians in terms of their origin, and in terms of the languages ​​contained therein, and in terms of their meaning and provisions And (Rubba) is one of the letters of meanings that scholars have spoken about a lot, and I have tried in this research to collect all the provisions related to it, trying to extrapolate the books of meanings, and he wrote the grammar that I dealt with mentioning between a summary and a sentence in talking about it. I tried to collect all the provisions related to it in this research, and shed light on the difference of scholars regarding it and its provisions. I have made the title of the research "(Rubba) of its rulings and grammatical opinions in it", and I have used the two approaches: descriptive and analytical in the research treatment, and the study reached several results, came at the conclusion of the research, and several sources informed us about weighting opinions, and issuing judgments related to the letter under study.